Can theory of Heritage help peace? - Šola, Tomislav (2005)
Peace museums, memory museums, human rights museums, anti-war museums supposed to play important role in the Word today, by propagating a culture of peace and reconciliation. Theory of Heritage could offer to mentioned institutions or projects (as well as to all people with a sympathetic interest to culture of peace) important knowledge, wisdom - which as result could lead us to the better future.